An insight into dentin desensitizing agents - In vivo study - Purvi Mehta; N Vimala; Lalitagauri Mandke (Wolters Kluwer Medknow Publications, 2013)
Aims: It is widely accepted that dentin hypersensitivity is an uncomfortable condition, which affects the function and quality of life. This study determines the difference in efficacy of four desensitizing agents. Subjects and Methods: An in vivo study was conducted to compare four dentin desensitizing agents on 40 patients. Age, sex, and place of the patient were recorded. Hydroxyapatite containing agent, potassium nitrate containing, sodium fluoride containing, and natural resin containing agents were used for the study. The baseline measurement for pain perceived due to hypersensitivity was recorded by visual analog scale (VAS). Then after application of the respective desensitizing agent, the last score was taken after 7 days. Statistical Analysis Used: The agents were compared in terms of mean differences in their VAS scale readings. Kruskall-Wallis test and Mann-Whitney tests were used to compare the efficacies of the four agents. Results: The four desensitizing agents which contain different active agents were effective in relieving dentin hypersensitivity. Not much significant difference was found among the four. However, propolis (natural resin-containing agent) showed better clinical response in patients among the four, followed by sodium fluoride-containing agent. Conclusions: Propolis proves to be a good natural and nontoxic option for treatment of dentin sensitivity.